2017
DOI: 10.1128/cvi.00172-17
|View full text |Cite
|
Sign up to set email alerts
|

Protein Malnutrition Alters Tryptophan and Angiotensin-Converting Enzyme 2 Homeostasis and Adaptive Immune Responses in Human Rotavirus-Infected Gnotobiotic Pigs with Human Infant Fecal Microbiota Transplant

Abstract: Malnutrition leads to increased morbidity and is evident in almost half of all deaths in children under the age of 5 years. Mortality due to rotavirus diarrhea is common in developing countries where malnutrition is prevalent; however, the relationship between malnutrition and rotavirus infection remains unclear. In this study, gnotobiotic pigs transplanted with the fecal microbiota of a healthy 2-monthold infant were fed protein-sufficient or -deficient diets and infected with virulent human rotavirus (HRV). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 69 publications
4
55
0
Order By: Relevance
“…4). Moreover, ACE2 is also related to adaptive immune responses [17]. In this current study, GSEA analysis showed that the high expression of ACE2 was related to innate immune responses, adaptive immune responses, B cell regulation and cytokine secretion, as well as an enhanced inflammatory response induced by IL-1, IL-10, IL-6, IL-8.…”
Section: Regulation Network After Infectionsupporting
confidence: 52%
“…4). Moreover, ACE2 is also related to adaptive immune responses [17]. In this current study, GSEA analysis showed that the high expression of ACE2 was related to innate immune responses, adaptive immune responses, B cell regulation and cytokine secretion, as well as an enhanced inflammatory response induced by IL-1, IL-10, IL-6, IL-8.…”
Section: Regulation Network After Infectionsupporting
confidence: 52%
“…With parental consent, sequential fecal samples were collected from a healthy, 2-monthold, exclusively breastfed, vaginally delivered infant. Samples were pooled and diluted to 1:20 (wt/vol) in PBS containing 0.05% (vol/vol) cysteine and 30% glycerol and stored at −80 • C as described previously (11,12).…”
Section: Human Infant Fecal Microbiota (Hifm)mentioning
confidence: 99%
“…The cell-culture adapted attenuated HRV (AttHRV) Wa G1P [8] strain passaged in African green monkey kidney cells (MA-104) was used as a vaccine at a dose of 1 × 10 7 fluorescent foci-forming units (FFU) (25). The Gn pig passaged virulent HRV (VirHRV) Wa strain at pig passage 26 was used as challenge virus at a dose of 1 × 10 6 FFU as described previously (11,12).…”
Section: Virusmentioning
confidence: 99%
See 2 more Smart Citations